Working Memory Capacity and Semantic-Morphosyntactic Competition: A Comparison of L1 and L2 Sentence Processing - Mohammad Hadi Mahmoodi; Hamidreza Sheykholmoluki (Journal of English Language Teaching and Learning, 2022)
This study explored the competition between semantic and morphosyntactic processing in L1 and L2. In addition, the relationship between working memory capacity (WMC) and L2 semantic-morphosyntactic processing was scrutinized. To this purpose, 73 Persian learners of English as a Foreign Language (EFL) participated in an offline grammaticality judgment test (GJT), an L1 as well as an L2 semantically-primed test, and a WMC test. The results showed that L1 morphosyntactic processing was not affected by semantic priming. But, L2 morphosyntactic parsing decisions, irrespective of the participants’ WMC, was significantly influenced by semantic priming, indicating that L2 morphosyntactic knowledge in learners' interlanguage system might be shaky and subject to communicative aspects of input. Additionally, the findings revealed a significant relationship between the participants' WMC and their L2 semantic/morphosyntactic processing. The findings of the study provide some implications for foreign language teachers with regard to teaching morphosyntactic aspects of language and correcting morphosyntactic errors.